EVALUASI KINERJA RUTTING HOT MIX ASPHALT - Susanto, Hery Awan; Pamudji, Gandjar; Mulyono, Bagyo (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 24, No. 2, Juli 2020, 2021)
One type of road damage is rutting (deformation). Rutting is a road structural damage that can interfere with traffic comfort. Rutting is an important factor to consider in asphalt mixtures. The cause of deformation is the shear strain that occurs in flexible pavement structures. In this study, the deformation behavior of flexible pavements was evaluated through simulation testing in the laboratory using the Hamburg Wheel Tracking Device (HWTD) and the Scaled Accelerated Load Simulator Device (SALSD). The correlation of the two types of simulation testing is analyzed to obtain the conversion factor (FI) value by considering the parameters of temperature, test speed, representative loading frequency and dynamic modulus of the Hot Mix Asphalt (HMA) mixture. The results of this study indicate a rutting correlation between HWTD and SALSD at different temperatures. The conversion factor of HWTD to SALSD is 0.93. From the analysis, it can also be concluded that the increase in the rutting value of the HMA material causes a reduction in the effectiveness of the conversion factor between the two tests.